Investigation of pathology, expression and proteomic profiles in human TREM2 variant postmortem brains with and without Alzheimer's disease. (29th April 2020) - Toomey, Christina E.; Heywood, Wendy; Benson, Bridget C.; Packham, Georgia; Mills, Kevin; Lashley, Tammaryn
Abstract: Triggering receptor expressed on myeloid cells 2 TREM2 was identified as a risk factor for late onset Alzheimer's disease (AD). Here we compared TREM2 cases with a variant ( TREM2 + ) and cases without a TREM2 variant ( TREM2 − ), considering pathological burden, inflammatory response and altered canonical pathways and biochemical functions between the cohorts. We hypothesised that TREM2 + cases would have a loss of function, indicating an altered inflammatory profile compared to TREM2 − cases. Immunohistochemistry was performed using antibodies against Aβ, tau and microglia markers in TREM2 + cases, with and without AD, which were compared to sporadic TREM2 − AD, familial AD and neurologically normal control cases. Aβ and tau load were measured along with the composition of Aβ plaques, in addition to microglial load and circularity. Expression and proteomic profiles were determined from the frontal cortex of selected cases. TREM2 + control cases had no Aβ or tau deposition. No differences in the amount of Aβ or tau, or the composition of Aβ plaques were observed between TREM2 + and TREM2 − SAD cases. There were no differences in microglial load observed between disease groups. However, the TREM2 + SAD cases showed more amoeboid microglia than the TREM2 − SAD cases, although no differences in the spatial relationship of microglia and Aβ plaques were identified. Visualisation of the canonical pathways and biological functions showed differences between the disease groups and the normal controls, clearly showing a number of pathways upregulated in TREM2 + SAD, TREM2 − SAD and FAD groups whilst, the TREM2 + controls cases showed a downregulation of the majority of the represented pathways. These findings suggest that the TREM2 + control group, although carrying the TREM2 + variant, have no pathological hallmarks of AD, have altered microglial and expression profiles compared to the TREM2 + SAD cases. This indicates that other unknown factors may initiate the onset of AD, with TREM2 influencing the microglial involvement in disease pathogenesis.